Problematic internet use and online sexual offending: a case study of strategic psychotherapy. - Saladino, Valeria; Calaresi, Danilo; Verrastro, Valeria; Lauriola, Marco; Mosca, Oriana (Sexual & Relationship Therapy, 2025)
Problematic internet use is increasingly prevalent today, posing significant challenges to mental health. This case study delves into the intricate relationship between problematic internet use and its potential escalation into online sexual offending involving CSAM. It focuses on an Italian 19-year-old who is convicted for such offense. The participant took part in a structured intervention involving four modules and 10 sessions of strategic psychotherapy aimed at sex offending behaviors. This mixed-method intervention addressed crucial objectives: initial assessment, building therapeutic alliance, addressing internalized stigma, fostering accountability for the offense, promoting therapeutic restitution, and conducting a 3-month follow-up evaluation. The participant's journey through these modules demonstrates considerable advancement in self-awareness, comprehension of his offense, and the implementation of coping strategies. His active involvement and openness to the therapeutic process reflect his dedication to personal development and rehabilitation. This case study underscores the effectiveness of strategic psychotherapy in facilitating internal locus of control and stigma processing surrounding online sexual offending behaviors among justice-involved individuals (JIIs). It highlights the importance of personalized interventions in facilitating rehabilitation and reducing the risk of recidivism in this challenging population. LAY SUMMARY: In this study, Federico (fictitious name), a 19-year-old from Italy, underwent strategic therapy while in a correctional facility for online sexual offending involving CSAM. The therapy helped him understand his actions, take responsibility, and work toward rehabilitation, showing that targeted therapy can reduce the risk of reoffending